Stimulation of functional recovery via neurorepair mechanisms by the traditional Japanese Kampo medicine, Ninjin'yoeito, and physical exercise in a rat ischemic stroke model. (10th February 2023) - Tani, Akira; Sakakima, Harutoshi; Otsuka, Shotaro; Mizuno, Keita; Nakanishi, Kazuki; Norimatsu, Kosuke; Takada, Seiya; Matsuoka, Teruki; Matsuzaki, Ryoma; Nakakogawa, Tomomi; Maruyama, Ikuro
Abstract: Ethnopharmacological relevance: Ninjin'yoeito (NYT), a traditional Japanese Kampo medicine consisting of 12 herbs, has been reported to improve cognitive dysfunction, depression, and neurological recovery in patients with neurovascular diseases such as Alzheimer's disease and stroke. Several studies have reported that the NYT components exert neurotrophic, neurogenic, and neuroprotective effects. In addition, exercise enhances neuroprotection and functional recovery after stroke. Rehabilitative exercises and pharmacological agents induce neurophysiological plasticity, leading to functional recovery in stroke patients. These reports indicate that NYT treatment and exercise may promote functional recovery following stroke through their beneficial effects. However, no study has determined the effects of NYT and the possible mechanisms of neurorepair and functional recovery after stroke. Aim of the study: This study aimed to investigate the combined effects of NYT and exercise on neuroprotection and functional recovery and the underlying mechanisms in a rat ischemic stroke model. Materials and methods: Stroke was induced with 60-min middle cerebral artery occlusion (MCAO) followed by reperfusion in adult male Sprague-Dawley rats. After stroke, the rats were assigned to four groups: ischemia reperfusion (IR), NYT, exercise (Ex), and NYT + Ex. NYT-treated rats were fed a diet containing 1% NYT one day after stroke. Exercise was performed using a motorized treadmill for 5 days a week (8–15 m/min, 20 min/day), starting 3 days after stroke. The NYT treatment and exercise were continued for 4 weeks after the stroke. Infarct volume, neurological deficits, sensorimotor functions, expression of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), tropomyosin receptor kinase A (TrkA) and B (TrkB), caspase-3 activity, and the p-Akt/Akt ratio were examined by immunohistochemistry and western blotting. Results: Compared to the IR group, all treated groups indicated reduced infarct volumes. The NYT + Ex group showed significantly improved waking time and beam walking score compared with the IR group. The expression of NGF/TrkA/p-TrkA and BDNF/TrkB was significantly increased in the NYT + Ex group compared with those in the IR group, whereas the number of caspase-3 positive cells around the lesion was significantly lower in the NYT + Ex group than in the IR group. In addition, the ratio of p-Akt/Akt was significantly higher in the NYT + Ex group than in the IR group. Conclusions: This study suggests that NYT in combination with exercise provides neuroprotective effects and improves sensorimotor function by stimulating NGF/TrkA and BDNF/TrkB, and by activating the Akt pathway in ischemic stroke of rats. NYT may be an effective adjunctive agent in post-stroke rehabilitation. Graphical abstract: Image 1 Highlights: Ninjin'yoeito and/or physical exercise provide neuroprotection, enhance neuronal plasticity, reduce apoptotic activity, and improve sensorimotor function after stroke. Ninjin'yoeito and/or physical exercise stimulated the expression of neurotrophic factors NGF/TrkA and BDNF/TrkB and by activating the Akt pathway. Ninjin'yoeito in combination with exercise, may have potential acute therapeutic effects after stroke.